Characterization of a Novel Wheat–Agropyron cristatum 2P Disomic Addition Line with Powdery Mildew Resistance. Issue 5 (1st September 2016) - Li, Qingfeng; Lu, Yuqing; Pan, Cuili; Zhang, Jinpeng; Liu, Weihua; Yang, Xinming; Li, Xiuquan; Xi, Yajun; Li, Lihui
Abstract : Agropyron cristatum (L.) Gaertn. (2 n = 4 x = 28; genomes PPPP) is one of the wild species closely related to cultivated wheat ( Triticum aestivum L.), which possesses a number of superior agronomic traits and thus represents a valuable resource for wheat improvement. Development of wheat– A. cristatum addition lines is usually considered to be the first step in transferring desirable alien genes into common wheat from A. cristatum . In this study, we report a novel wheat– A. cristatum 2P disomic addition line II‐9‐3, which contained 42 wheat chromosomes and a pair of A. cristatum chromosomes as revealed by genomic in situ hybridization. The homoeologous relationship between A. cristatum and wheat chromosomes was determined using specific‐locus amplified fragment sequencing markers specific to the A. cristatum 2P chromosome. Moreover, II‐9‐3 displayed high resistance to powdery mildew at both seedling and adult stages. Genetic analysis was conducted using an F2 population made by crossing II‐9‐3 with the susceptible cultivar Fukuhokomugi (Fukuho), and the results indicated that powdery mildew resistance was attributable to A. cristatum 2P chromosome in II‐9‐3. Besides, the resistance spectrum of II‐9‐3 was quite broad, as it was found resistant to all the 17 Bgt isolates prevalent in northern China. Taken together, this study will provide applicable methods for both genetically characterizing wheat addition lines with alien chromosomes and also novel germplasm potentially valuable in wheat resistance breeding.